A review: methods of determination of health-endangering formaldehyde in diet - Marzuki, Nur Indang; Abdulamir, Ahmed Sahib; Abu Bakar, Azuraliza; Salleh, Abu Bakar; Lee, Yoon Hee; Yusof, Nor Azah (Medwell Journals, 2009)
The sea food immersed with formaldehyde to prevent spoilage by dishonest fish mongers is a big risk to the health of consumers especially risk of cancer development. Formaldehyde is a toxin for viable cell. With increasing awareness of food safety and authenticity issues, new and sophisticated techniques for the authentication of seafood are developed. Therefore, many methods are proposed to assure the quality of seafood by determining the formaldehyde content. Various ranges of methods have been proposed such as colorimetric method to high technology device methods and E-nose has been applied in seafood. Specificity, simplicity and quick response of the method is most considered to choose for application in situ. This review demonstrates the potential of technological applications have so far been used in determining formaldehyde in seafood and their setbacks, disadvantages and advantages. This review is aimed to be as a reference of formaldehyde detection techniques in seafood.